The Relations Between Wind Speed and Discharge on Wind Pump for Irrigation Purpose The case study in Setro’s Reservoir - Benny Syahputra (International Conference on Coastal and Delta Areas, 2015)
To irrigate thier rice fields, farmers in Gedangan village of Rembang District, North-East of Central Java Province take water from Setro’s reservoir. Since the surface level of water in the reservoir lower than the elevation of the fields, the farmers must use water pump to elevate the water into the higher level to the fields. Data from the Institute for Environment and Agricultural Research (2010) show that the annual average wind speed in Gedangan village is minimum 2.3 meter/secondand maximum is 9.2 meter/second. Based on those wind speed data, it can be used as a power of water pump by constructing windmill. The research shows that the wider leaf of windmills the more discharge of water can be resulted. However, there is optimum wide of windmill leaf. If the optimum wide of leaf over, the discharge will decrease. increased along with the increase in the diameter of the blade, but the discharge will back down if the blade diameter is enlarged after the maximum discharge.